China's Trade Slowdown: Cyclical or Structural?. Issue 6 (16th November 2017) - Qian, Xuefeng; Liu, Zhao; Pan, Ying
Abstract: This paper analyzes whether the slowdown of China's trade in 2012–2015 was cyclical or structural, and further discusses the effects of structural factors, including trade structure, trade protectionism and global value chain participation. Using the national panel data from 2000 to 2015, based on the error correction model and import‐intensity‐adjusted demand model, our results show that the slowdown of China's trade growth in 2012–2015 was mainly a result of cyclical factors. Using 2000–2015 industry‐level data, we also find that the structure of trade goods had an inhibitory effect on the import slowdown but a positive effect on the export slowdown. Trade protectionism had an adverse effect on the trade growth slowdown. The global value chain participation marginally contributed to the slowdown in trade growth. Therefore, the impacts of structural factors on trade growth slowdown cannot be ignored, and related policies should receive greater attention from policy‐makers.